Determinan Pendapatan Asli Daerah Kabupaten atau Kota di Jawa Tengah Tahun 2017-2020 - Putri Rarasati; Sitti Retno Faridatussalam (Universitas Batanghari Jambi, 2022)
Local revenue is one of the main sources in carrying out development in each region. Regions cannot rely on funding sources from the center due to the limited funds they have. This study aims to determine the effect of the number of workers, consumer price index, investment, and the regional minimum wage on the original income of the Regency or City in Central Java in 2017-2020 by using panel data regression. The results with the Fixed Effects approach show that the number of workers has a negative effect on regional original income and the regional minimum wage has a positive effect on regional original income. Meanwhile, investment and the consumer price index were found to have no effect on the original income of districts or cities in Central Java Province in 2016-2020. The government is expected to improve the economy so that it can attract investors to invest their capital. In addition, the control of commodity prices for goods and services needs to be improved so that the public can still reach the rising prices.